Correction of Glycogen Synthase Kinase 3β in Myotonic Dystrophy 1 Reduces the Mutant RNA and Improves Postnatal Survival of DMSXL Mice - Wang, Mei (Mol Cell Biol, 2019)
Myotonic dystrophy type 1 (DM1) is a multisystem neuromuscular disease without cure. One of the possible therapeutic approaches for DM1 is correction of the RNA-binding proteins CUGBP1 and MBNL1, misregulated in DM1. CUGBP1 activity is controlled by glycogen synthase kinase 3β (GSK3β), which is elevated in skeletal muscle of patients with DM1, and inhibitors of GSK3 were suggested as therapeutic molecules to correct CUGBP1 activity in DM1. Here, we describe that correction of GSK3β with a small-molecule inhibitor of GSK3, tideglusib (TG), not only normalizes the GSK3β-CUGBP1 pathway but also reduces the mutant DMPK mRNA in myoblasts from patients with adult DM1 and congenital DM1 (CDM1). Correction of GSK3β in a mouse model of DM1 (HSA(LR) mice) with TG also reduces the levels of CUG-containing RNA, normalizing a number of CUGBP1- and MBNL1-regulated mRNA targets. We also found that the GSK3β-CUGBP1 pathway is abnormal in skeletal muscle and brain of DMSXL mice, expressing more than 1,000 CUG repeats, and that the correction of this pathway with TG increases postnatal survival and improves growth and neuromotor activity of DMSXL mice. These findings show that the inhibitors of GSK3, such as TG, may correct pathology in DM1 and CDM1 via several pathways.